Use of selenium to ameliorate doxorubicin induced hepatotoxicity by targeting pro-inflammatory cytokines. (2nd January 2021) - Cengiz, Ozge; Baran, Munevver; Balcioglu, Esra; Suna, Pinar Alisan; Bilgici, Pınar; Goktepe, Ozge; Onder, Gozde Ozge; GOC, Rumeysa; Yay, Arzu
ABSTRACT: Doxorubicin (DOX) is a widely used drug for the treatment of cancer, but its clinical use is limited by its liver toxicity. Administering DOX with an antioxidant has become a strategy for preventing the side effects of DOX. Although selenium (Se) is an important trace mineral, data concerning the effect of Se on DOX induced liver tissue are lacking. We investigated the mechanism of DOX hepatotoxicity and the protective effect of different doses of Se on Dox induced liver damage. Female Wistar albino rats were divided into eight equal groups. Se was injected intraperitoneally (i.p.) to rats at doses of 0.5, 1, and 2 mg 0.5 h after injection i.p. of 5 mg/kg DOX on days 1, 7, 14, 21 and 28. Liver histopathology was assessed to determine the dose at which Se may best inhibit Dox induced liver toxicity. Also, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) expression levels and proliferating cell nuclear antigen (PCNA) activity were determined using immunohistochemistry. We found that DOX caused liver damage and increased TNF-α, IL-1β and PCNA levels. Se prevented structural damage to liver tissues. Our findings reinforce the protective effects of Se in rat liver.